Lost in Theorization: On the Effectiveness of Policies to Promote Creative Industries in Peru - Durand Grahammer, Juan Carlos (2017)
Starting from the concept of creative industries, this article focuses on the potential of intellect and creativity as key factors for development and creation of wealth in Peru.Attention is paid to how the implementation of development policies in the field of creative industries presents itself in Peru. This article reviews diverse data representing different manifestations of creative industries, and the analysis thereof shows two things: on the one hand, the Peruvian State insists on deploying scarce resources to these areas, and, on the other hand, it gets lost in projects which due to their disconnection from experience and practice of local organizations and initiatives end up being too distant from the reality in Peru. Finally, this article provides proposals, in particular the Internet as platform for development and diffusion of intellect in Peru.